Rainfall infiltration through unsaturated layered soil column - Aniza Ibrahim,; Muhammad Mukhlisin,; Othman Jaafar, (Universiti Kebangsaan Malaysia, 2014)
Infiltration caused by rainfall will lead to the changes of moisture content and soil pore water pressure or matric suction of the soil. These changes indicate the behavior of the soil especially during wetting and drying process. This paper presents the experimental test result of rain water infiltration into soil column for two samples of soils. The main objectives were to study the effect of rainfall intensity and duration of soil infiltration process for the forest soil and to compare its result to the gravelly sand. Infiltration experimental in this study involved three main components; water supply system, soil column and instrumentations, including percolation collection system. This study uses two types of tensiometers; 5 and 10 cm long. The results of TDR and tensiometers which were used to obtained moisture content and matric suction, respectively, shows that the system was successfully developed. For the forest soil, the result showed that moisture content of the top section is higher compared with the other sections. On the other hand, for gravelly sand, the moisture content in middle section is higher compared with the top and bottom section of the soil. Meanwhile, matric suction for both soils dropped during rainfall and gradually increases towards drying process. Other than that, the comparison of soil matric suction between 5 and 10 cm tensiometers shows significant results for gravelly sand compared to forest soil.